Sistem Pendukung Keputusan Penentuan Lokasi Promosi Mobil Dengan Menggunakan Metode WASPAS - Yovi Rivaldi (Bulletin of Information System Research, 2023)
The problem that occurs at PT.Arista Auto Lestari Sisingamangaraja Branch is that it has not been able to determine the location of a computerized car promotion because so far to determine the location of a car promotion only based on relations and price without taking into account the purchasing power of visitors and shopping intensity so that the expected turnover is rarely fulfilled. So to solve the problem at PT.Arista Auto Lestari Sisingamangaraja Branch it is necessary to improve the computerized system, so that in the future to determine the location of car promotions is no longer from relations or acquaintances but has been computerized by determining alternative locations and also predetermined criteria, such as the number of visitors per day, purchasing power, area area, visitor interest, visitor economic level and so on, it is necessary to create a decision support system by applying the Waspas method. The application of the Waspas method in the decision support system application to determine the location of car promotions at PT.Arista Auto Lestari Sisingamangaraja Branch first establishes the criterion value for each alternative location, after it is known, the next step is to apply the Waspas method, where the Waspas method process can provide the right decision . The application used is desktop-based using Visual language, so the results of the program implementation process are as expected.